Soybean as an alternative nutrient medium for Bacillus subtilis growth - Nurul Hanisah Abdul Malik; Khanom Simarani; Muhamad Afiq Aziz (Penerbit Universiti Kebangsaan Malaysia, 2022)
Nutrient agar is a commonly used medium for the isolation and growth of a broad range of microorganisms. The feasibility of using soybean as a base medium in the development of alternative growth media was assessed in this study. Nutrient agar was used as a standard guide to evaluating the performance of the formulated soybean agar. Bacillus subtilis was inoculated and allowed to grow on nutrient agar and soybean agar. Their growth was compared within 24 h after inoculation based on the morphology of individual colonies formed on both media and the pattern of bacterial growth. Our results showed that soybean agar had comparable performance to nutrient agar as the morphological characteristics of B. subtilis colonies formed on both media are generally identical in terms of texture, margin, optical properties, colour, elevation, and shape. However, due to the similar appearance of the bacterial colonies and the soybean agar, the colonies formed on the soybean agar were slightly larger than those formed on nutrient agar. In addition, our findings also revealed that agar strips formed the best soybean agar compared to gelatin and agar powder. Ultimately, this study has shown that locally available soybeans and agar strips can be easily formulated as an alternative to commercial nutrient agar and have great potential for bacteriological research.